The Lithuanian Case of Higher Education Reforms in Europe - Leisyte, Liudvika (International Higher Education, 2008)
The Bologna process has spurred higher education reforms in various European countries. Higher education reforms in Lithuania took place rather incrementally and represented an interaction between two strong powersthe state and the academic oligarchy. In the 1990s, the structural changes at the forefront of the Bologna-related reforms in Lithuania, but higher education reforms have remained stagnant in Lithuania. It is too early to draw conclusions about the success of the reforms, but the involvement of various stakeholders and the vision of broad reforms increase hopes for prospects of a more radical change of the Lithuanian higher education landscape.